RELIGION AS AN INSTRUMENT OF EXPLOITATION: A PSYCHOANALYTICAL PERSPECTIVE IN THE SELECT NOVELS OF MULK RAJ ANAND - R. Esther Reshma; Bharathiraja, S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study analyzes Mulk Raj Anand’s aim on exposing the fraudulence that has crept into the practice of religions. Regarding Hinduism, Anand’s main target of attack is its caste system. He finds the division of society on the basis of caste abominable. In the earlier days, the caste system has been based on the division of labour. Later on, it has been degenerated into a system in which the Brahmins, the Kshatriyas and Vaishyas look down upon the lower castes. They do not even like to touch the sweepers or to be touched by them. Like Untouchable, The Village also reveals the miserably unhygienic living conditions of the sweepers. They live inhaling the most obnoxious and rotten air of the most foully odorous pond in the midst of the dirt of the city. Almost the same miserable unhygienic conditions prevail in The Road. The upper caste people have a sense of superiority. The Brahmins, the Kshatriyas, the two upper castes in Hindu society, justify their superiority by asserting that they have earned their position by the good-deeds of multiple lives. In The Road, the outcastes are not permitted to enter the holy shrines. Pandit Suraj Mani bars the way of the Untouchables by joining hands with the caste Hindus when they want to worship. The Untouchables are deprived of some of the most 27 essential needs of human life and by this deprivation they are made abject and servile. One such thing is the denial of education. Bakha views education as a means to escape from his hereditary profession. In Coolie Prabha Dayal is unable to pay back his creditors as he has been cheated by his partner Ganpat. In the initial stage Prabha does not realize that his partner is wicked. Mulk Raj Anand’s condemnation of the exploitation indulged in by the British capitalists is revealed through the unhappy and miserable life that the native workers are made to lead in the cotton mill in Coolie and tea-plantations in Two Leaves and a Bud.